THU0460 IDENTIFICATION OF POSTOPERATIVE PAIN BIOMARKERS USING GENE EXPRESSION ANALYSES IN THE PERIPHERAL BLOOD OF OSTEOARTHRITIC PATIENTS PRIOR TO JOINT REPLACEMENT. (June 2019) - Tchetina, Elena; Glemba, Kseniya; Makarov, Sergey
Abstract : Background: Osteoarthritis (OA) is a chronic rheumatic disease, which involves pain, limited inflammation and local destruction of the knee joint. OA pain is a major clinical symptom, which limits working capacity and denotes an important indication for joint replacement in the end-stage OA. In spite of significant number of positive outcomes, chronic postoperative pain represents a major adverse consequence of surgery, which is observed in 10-40% of OA patients. Therefore, identification of patients potentially capable of developing chronic postoperative pain prior to surgery could significantly improve therapy outcome. Central sensitization is in charge of pain symptoms in about 30% of end-stage OA patients. Several recently identified molecular markers such as cytokines, chemokines, calcium and glutamate transporters, caspases, and proteases has been shown to be responsible for central sensitization. Therefore, we hypothesized that genes related to pain sensitization whose expression is upregulated in about 30% of the examined end-stage OA patient cohort might be responsible for postoperative pain. Objectives: To outline an approach for search of biomarkers related to chronic postoperative pain development before joint replacement in the peripheral blood of end-stage OA patients. Methods: We examined peripheral blood of 26 healthy volunteers (average age 55±8.3 years old) and 53 end-stage OA patients (average age 56.5±8.9 years old) undergoing joint replacement surgery. MMP-9, TIMP1, TGFβ1, and caspase 3 protein levels were quantified by ELISA. Total RNA isolated from whole blood was used in expression studies for the genes related to central sensitization such as mechanistic target of rapamycin, mTOR; caspase 3; metalloproteinase (MMP)-9; tissue inhibitor of metalloproteinase TIMP1; cathepsins K and S; interleukin (IL)-1β; cyclooxygenase (COX)2; tumor necrosis factor (TNF)α, and transforming growth (TGF)β1. These were performed with quantitative real-time RT-PCR. Results: Retrospective analysis of gene expression in the peripheral blood of end-stage OA patients before joint replacement surgery revealed that gene expression data for TNFα, IL-1β, COX2, TGFβ1, and mTOR were not applicable as these gene expressions were significantly higher compared to healthy controls in all the examined OA patients. High expression of pain associated cathepsin S in 17% of the examined OA patients and cathepsin K, in 21% might indicate the possibility of postoperative pain development in these OA patients. In contrast, low expression of caspase 3 in 43% of the examined OA patients and MMP-9, in 23%, might point toward the absence of postoperative pain in these subjects. Conclusion: Gene expression analysis in the peripheral blood of the end-stage OA patients measured before joint replacement surgery might represent an approach for prediction of postoperative pain development. Disclosure of Interests: : None declared